2015
DOI: 10.1371/journal.pone.0129944
|View full text |Cite
|
Sign up to set email alerts
|

Novel Kidins220/ARMS Splice Isoforms: Potential Specific Regulators of Neuronal and Cardiovascular Development

Abstract: Kidins220/ARMS is a transmembrane protein playing a crucial role in neuronal and cardiovascular development. Kidins220/ARMS is a downstream target of neurotrophin receptors and interacts with several signalling and trafficking factors. Through computational modelling, we found two potential sites for alternative splicing of Kidins220/ARMS. The first is located between exon 24 and exon 29, while the second site replaces exon 32 by a short alternative terminal exon 33. Here we describe the conserved occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…SINO syndrome is characterized by spastic paraplegia, intellectual disability, nystagmus and obesity. The variants of KIDINS220 responsible for this sort of syndrome were closely related to an isoform of KIDINS220 with alternative splicing and present only in adult tissues . The study has shown the importance of the delicate balance of KIDINS220 isoforms' expression during the developmental phases of an embryo .…”
Section: Kidins220/arms and Human Diseasesmentioning
confidence: 84%
See 1 more Smart Citation
“…SINO syndrome is characterized by spastic paraplegia, intellectual disability, nystagmus and obesity. The variants of KIDINS220 responsible for this sort of syndrome were closely related to an isoform of KIDINS220 with alternative splicing and present only in adult tissues . The study has shown the importance of the delicate balance of KIDINS220 isoforms' expression during the developmental phases of an embryo .…”
Section: Kidins220/arms and Human Diseasesmentioning
confidence: 84%
“…The variants of KIDINS220 responsible for this sort of syndrome were closely related to an isoform of KIDINS220 with alternative splicing and present only in adult tissues. 46 The study has shown the importance of the delicate balance of KIDINS220 isoforms' expression during the developmental phases of an embryo. 45 Other genetic variants were found in unborn fetuses corresponding to a premature termination codon in exon 25 resulting in nonsense-mediated mRNA decay and absence of protein.…”
Section: Ki DI N S2 20 /A Rm S a N D Hu M A N Di S E A S Esmentioning
confidence: 99%
“…Kidins220 is an integral membrane protein essential for neurotrophin signaling that interacts both with Trks and p75 NTR . Recent studies have revealed that Kidins220 shows alternative splicing variants determining the presence or the absence of critical protein–protein interaction domains, which may cause still unexplored structural and functional changes . Specifically, in mouse and human adult brain, Kidins220 presents two main isoforms as the result of alternative terminal exon splicing from exon 31 to exon 32 or to exon 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that Kidins220 shows alternative splicing variants determining the presence or the absence of critical protein–protein interaction domains, which may cause still unexplored structural and functional changes . Specifically, in mouse and human adult brain, Kidins220 presents two main isoforms as the result of alternative terminal exon splicing from exon 31 to exon 32 or to exon 33 . These variants, known as full length and C2 and here respectively named Kidins220‐C32 and Kidins220‐C33, strongly differ in their carboxy‐terminal (C‐terminal) length and sequences .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation